The role of communication style in adaptation to interorganizational project disruptions. Issue 4 (11th May 2022) - Oliveira, Nuno; Argyres, Nicholas; Lumineau, Fabrice
Abstract: Interorganizational projects often suffer disruptions that require participating organizations to adapt in order to restore project operations. We study the role of communication style in facilitating adaptation to such disruptions. Whereas the literature on interorganizational communication has emphasized communication mode and frequency, we study the content and features of written communication in seven U.K. construction projects. Communication style mattered for adaptation quality in these projects, and we found that several properties of communication style were particularly important for adaptation: cost and information orientation, as well as informality, precision and authenticity. Moreover, managerial slack and organizational reputation were important precursors of communication style. These results provide novel insights into the role of communication style in adaptation to interorganizational project disruptions. We discuss the implications of these insights for research on interorganizational projects in operations and supply chain management.